Ultrasound‐guided sacral multifidus plane block for analgesia following excision of sacrococcygeal teratoma in two neonates. Issue 1 (27th April 2021) - Mahajan, R.; Gulati, S.; Gupta, K.; Jain, K.; Bloria, S.; JItendra, M.
Summary: Peri‐operative pain management in the neonate with a sacrococcygeal teratoma poses significant challenges to the anaesthetist. Involvement of the sacrococcygeal area by the tumour often prevents the use of conventional regional anaesthetic techniques such as caudal or epidural analgesia, with a subsequent reliance on intravenous opioids and paracetamol. Since opioids are associated with respiratory depression, constipation and urinary retention, there is high incidence of opiophobia with consequent inappropriate dosage prescription, particularly in the paediatric population. We describe the use of an ultrasound‐guided sacral multifidus plane block in two neonates undergoing surgical excision of sacrococcygeal teratoma. The block is technically easy to perform and also avoids traversing critical structures. Hence, it may be regarded as a promising analgesic technique for painful interventions in the sacrococcygeal area.